2020
DOI: 10.7759/cureus.7007
|View full text |Cite
|
Sign up to set email alerts
|

Use of New Oral Anticoagulants/ Direct Oral Anticoagulants in Malignant Patients

Abstract: Vitamin K antagonists are being used in the last five decades as an effective anticoagulant. However, for the past few years, new oral anticoagulants (NOACs) have been introduced as newer anticoagulant agents, which are gradually replacing the previously used vitamin K antagonist. Yet, these agents have not fully replaced the use of warfarin and heparin. NOACs have few advantages over the vitamin K antagonist as they act on a specific factor of coagulation cascade rather than inhibiting the whole vitamin K syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…The previous study demonstrated that increased expression of thrombomodulin might reduce the migration of cancer cells by restraining PI3K and Akt [ 20 ]. Furthermore,increasing evidence showed that the anticoagulant drugs, such as warfarin and heparin, have antitumor effects both in vivo and in vitro [ 21 ]. Anticoagulants, especially the low molecular heparin, have a splendid antitumor effect without fatal bleeding and venous thromboembolism [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study demonstrated that increased expression of thrombomodulin might reduce the migration of cancer cells by restraining PI3K and Akt [ 20 ]. Furthermore,increasing evidence showed that the anticoagulant drugs, such as warfarin and heparin, have antitumor effects both in vivo and in vitro [ 21 ]. Anticoagulants, especially the low molecular heparin, have a splendid antitumor effect without fatal bleeding and venous thromboembolism [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Essa classe inovadora detém algumas vantagens em relação aos antagonistas da vitamina K, como um dose fixa sem a necessidade de verificação de coagulação rotineira e menor IMs, onde em estudo in vitro os ACODs exibem pouco efeitos nas enzimas-chave da CYP, não afetando parâmetros farmacocinéticos de outros fármacos. Estudos recentes, não mostraram riscos de sangramentos associados ao edoxaban oral em pacientes com câncer de pulmão, mama e ginecológico (Khan, et al, 2020;Mulder, et al, 2020).…”
Section: Discussionunclassified
“…Many antitumor drugs inhibit and compete with the cytochrome P-4503A4 enzyme (CYP3A4) or permeability glycoprotein transporter (P-gp). Thus, the simultaneous use of antitumor drugs and NOACs may cause drug-drug interactions, which may enhance anticoagulation of NOACs and thereby increase the risk of major bleeding (128)(129)(130). Meanwhile, the 2018 European Heart Rhythm Association Practical Guide also indicated that strong inhibitors of CYP3A4 or P-gp should not be used with NOACs in AF patients (128).…”
Section: Antithrombotic Therapy In Cancer Patients Comorbid With Af A...mentioning
confidence: 99%